Carbon Markets in African Livestock Sectors: A Scoping Study and Research Agenda - Jain, K.; Dokka, D.; Crane, Todd A. (International Livestock Research Institute, 2025)
The purpose of this report is to assess the impact of carbon financing projects on livestock producers in Africa, with a focus on the opportunities, risks, and challenges faced in integrating smallholder livestock producers into carbon credit markets. The report examines existing carbon finance mechanisms, evaluates their effectiveness, and explores potential models for scaling up participation among smallholder farmers. There is increasing potential for livestock-based carbon credit projects in Africa, particularly in areas where methane reduction strategies can be implemented. However, smallholder livestock producers face numerous challenges in accessing carbon markets, including a lack of technical expertise, limited financial resources, and complex certification processes. While carbon finance can provide an additional revenue stream, current pricing structures and verification costs often make it difficult for smallholder farmers to participate profitably. Inconsistent policies and a lack of government support further hinder the adoption of carbon finance initiatives for livestock producers. Some pilot projects have demonstrated the feasibility of integrating smallholder farmers into carbon finance mechanisms, but scalability remains a challenge due to funding and logistical constraints. Partnerships and collaboration between governments, private sector actors, and non-governmental organizations (NGOs) are critical for creating an enabling environment for smallholder participation. A summary of key points is given below: Projects emphasizing non-carbon outcomes have shown greater effectiveness compared to direct financial transfers to smallholder livestock producers, which have historically been inadequate and inconsistent. There is increasing skepticism regarding carbon credits among smallholder farmers and NGO partners in Africa. Carbon credit initiatives are advancing of relevant policy frameworks, notably in the livestock sector, which remains inadequately addressed in Nationally Determined Contributions (NDCs). Smallholder livestock producers face heightened risks of land appropriation, particularly within sustainable grazing-based carbon credit projects. The establishment of additional smallholder cooperatives and the creation of local Validation and Verification Bodies (VVBs) can significantly enhance the efficacy and credibility of carbon credits involving smallholder livestock producers.